Ant diversity patterns across tropical elevation gradients: effects of sampling method and subcommunity. Issue 8 (1st August 2019) - Longino, John T.; Branstetter, Michael G.; Ward, Philip S.
Abstract: Local diversity may be influenced by niche assembly processes involving competition for limited resources, or by niche conservatism and the length of time clades have had to diversify. Mid‐elevation peaks in ant diversity on wet forest elevational gradients are most consistent with niche conservatism effects. However, it is possible that subsets of the ant community vary in the degree to which niche assembly processes are important, and this may be revealed by sampling methods that bias toward particular subsets. A previous study of ant‐elevation patterns in Middle American wet forest relied on Winkler sampling, a method that samples much of the ant community that occurs in leaf litter and rotten wood on the forest floor. Here, we evaluate richness patterns at the same sites as the previous study, using two alternative methods: baiting and beating. Baiting attracts ants to a concentrated resource and might be expected to attract a community more shaped by competitive interactions. Diversity patterns at baits were nearly identical to patterns from Winkler samples, for all ants combined and for the genus Pheidole, which are abundant omnivorous ants that are among the most common at baits. There was no evidence that stronger competitive effects influenced the shape of the diversity curve. Beating samples capture ants that forage on low vegetation, a distinct arboreal community with lower phylogenetic diversity than litter ants and inhabiting a more variable microclimate. Arboreal ants differed from litter ants in having a less distinct mid‐elevation peak, with less of a decline from 500 m to sea level. The lowland decline in litter ant diversity may be caused by the recent upslope shift in temperature associated with the current interglacial period. Arboreal ants may be buffered from this effect by adaptation to canopy life, tolerating broader extremes of temperature, or by high rates of dispersal from warmer regions.